Themes from Brentano - Fisette, Denis, 1954-; Fréchette, Guillaume, 1976- (Studien zur Österreichischen Philosophie, 2013)
Franz Brentano's impact on the philosophy of his time and on 20th-century philosophy is considerable. The "sharp dialectician" (Freud) and "genial master" (Husserl) influenced philosophers of various allegiances, being acknowledged not only as the "grandfather of phenomenology" (Ryle) but also as an analytic philosopher "in the best sense of this term" (Chisholm). The fourteen new essays gathered together in this volume give an insight in three core issues of Brentano's philosophy: consciousness (sect.1), intentionality (sect. 2) and ontology and metaphysics (sect. 3). Two further sections of the volume deal with the posterity of his philosophy: in section 4, the legacy of his account of sense perception and feeling is discussed, while the history of Brentano's unpublished manuscripts is discussed in section 5. This section also presents an edition of a manuscript from 1899 on relations, along with the letters from Brentano to Marty which discuss this manuscript. The last part of section 5 contains the tekst of a public lecture given by Brentano on the laws of inference.